Anthropology : appreciating human diversity - Kottak, Conrad Phillip (McGraw-Hill, 2013)
Offers a holistic introduction to general anthropology from the four-field perspective. This book focuses on an increasingly interconnected world, the Focus on Globalization essays examine topics as diverse as tourism in the ancient and modern worlds, global disease pandemics, world events and the expansion of international finance and branding